End-to-end QoS management for multimedia over IP - Zhan, Wenning (2008)
The objective of this research is to study, design and implement end-to-end QoS management schemes, particularly on congestion control and error control in the transportation layer, for multimedia communications over IP. In my two-year study, we focus on two theoretical problems, i.e., wireless link modeling and optimal retransmission timeout (RTO) selection, we also develop a practical RTP-based transportation system for multimedia streaming over IP with end-to-end QoS management.